The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.13080/z-a.2015.102.044
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of Alternaria species on cabbage in Iran

Abstract: In a study on Alternaria species, associated with cabbage black spot disease in Urmia, West Azerbaijan, Iran, cabbage fields were inspected during the growing seasons of 2012-2013 and leaves with suspected symptoms of Alternaria infection were collected. A total of 135 isolates with Alternaria characteristics were obtained from 10 main growing areas in this region and studied taxonomically. On the basis of morphological characteristics of the studied isolates, 8 species viz. Alternaria arbusti, A. brassicicola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Then these leaf bits were washed thrice in sterile water and placed aseptically on the sterile petriplate which was poured with the sterilized potato dextrose agar (PDA) medium (Rahimloo and Ghosta, 2015). These plates were incubated at room temperature (27±4 0 C) for proper development of the pathogen.…”
Section: Isolationmentioning
confidence: 99%
“…Then these leaf bits were washed thrice in sterile water and placed aseptically on the sterile petriplate which was poured with the sterilized potato dextrose agar (PDA) medium (Rahimloo and Ghosta, 2015). These plates were incubated at room temperature (27±4 0 C) for proper development of the pathogen.…”
Section: Isolationmentioning
confidence: 99%
“…Brassica seedlings are often infected by seedborne pathogens, especially by the serious pathogen Alternaria spp. in many countries (Kubota et al 2006;Rahimaloo & Ghosta 2015). This study, for the first time, isolated and characterised the pathogen of Alternaria leaf spot in broccoli in Bangladesh as A. alternata.…”
Section: Discussionmentioning
confidence: 96%
“…The fungus morphologically showed profuse mycelial growth on the PDA, turning grey–brownish [ 37 , 67 ] in colour, consistent with Woudenberg et al [ 19 ], and spores resembling those of A. alternata . Morphology was not the main means of identification, as Alternaria isolates could differ morphologically due to the different cultivating conditions and the overlap in the spore sizes of some species [ 68 ]. Armitage et al [ 69 ] reported that the morphological characteristics used to delineate species in Alternaria sect.…”
Section: Discussionmentioning
confidence: 99%